Republic of Moldova : 2010 Article IV Consultation and Staff Report for the 2010 Article IV Consultation, First Reviews Under the Extended Arrangement and Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of a Performance Criterion; Staff Report; Staff Statement and Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2010)
The Moldovan economy is recovering steadily following the recession triggered by the global crisis. The key challenge is to ensure fiscal, financial, and external sustainability while igniting new engines of growth. Monetary policy strikes the right balance between keeping inflation low and supporting the recovery. The monetary policy framework could benefit from more flexibility. Stepping up exports is a key to achieving high and sustainable growth over the medium term. Bringing the energy sector to financial sustainability should remain high on the government's agenda.